In Situ Placement Versus Anterior Transposition of the Ulnar Nerve for Distal Humerus Fractures Treated With Plate Fixation: A Multicenter Randomized Controlled Trial. Issue 9 (September 2021) - Dehghan, Niloofar; Nauth, Aaron; Hall, Jeremy; Vicente, Milena; McKee, Michael D.; Schemitsch, Emil H.
Abstract : Objectives: To compare clinical scores and electrodiagnostic evidence of ulnar neuropathy, between ulnar nerve mobilization and placement back in the cubital tunnel versus anterior transposition, during plate and screw fixation of a bicolumnar fracture of the distal humerus. Design: Multicenter randomized controlled trial. Setting: Eight tertiary care centres in Canada. Patients: Fifty-eight patients with distal humerus fractures undergoing plate fixation of both columns were recruited and randomized. Intervention: All patients underwent bicolumnar plate fixation for an acute, displaced fracture of the distal humerus with identification, mobilization, and protection of the ulnar nerve as part of the surgical approach. At the conclusion of the procedure, they were randomized to either (1) replacing the nerve in situ in the cubital tunnel or (2) anterior transposition. Main Outcome Measurements: The primary outcome was the Gabel & Amadio rating scale for ulnar neuropathy. Secondary outcomes included a functional outcome score (Mayo Elbow Performance Score), disabilities of the arm, shoulder and hand instrument, 2-point discrimination, nerve conduction testing, complications, and secondary surgeries. Results: Thirty-one patients were randomized to in situ placement and 27 to anterior transposition. The mean age was 53 years, and 60% were women. There was no difference between the 2 groups with regards to age, gender, body mass index, smoking, diabetes, injury characteristics, time to operation, length of operation, or surgical approach. There was no difference in outcome between the 2 groups at any time point with regards to Gabel & Amadio ulnar neuropathy scores, Mayo Elbow Performance Score, disabilities of the arm, shoulder and hand instrument, or 2-point discrimination. The incidence of ulnar nerve dysfunction, as measured by use of the Gabel & Amadio ulnar neuropathy score, was poor in both groups acutely; however, there was significant improvement at 12 months postoperatively (6.0–7.8, P < 0.001). Conclusions: This study was unable to demonstrate any significant difference in outcomes when comparing ulnar nerve mobilization and in situ placement and anterior subcutaneous transposition after bicolumnar plate fixation of a distal humerus fracture. Either strategy for managing the ulnar nerve is acceptable and can be used at the discretion of the treating surgeon. Level of Evidence: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.